2009
DOI: 10.1104/pp.109.143495
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Gene Programs by EMF1 and EMF2 in Arabidopsis    

Abstract: The EMBRYONIC FLOWER (EMF) genes are required to maintain vegetative development in Arabidopsis (Arabidopsis thaliana). Loss-of-function emf mutants skip the vegetative phase, flower upon germination, and display pleiotropic phenotypes. EMF1 encodes a putative transcriptional regulator, while EMF2 encodes a Polycomb group (PcG) protein. PcG proteins form protein complexes that maintain gene silencing via histone modification. They are known to function as master regulators repressing multiple gene programs. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
86
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 65 publications
7
86
1
Order By: Relevance
“…On the other hand, other results suggest that all these components are required for the regulation of a different subset of target genes. For instance, AtRING1A has been shown to participate in the repression of FLC, MAF4, and MAF5 (Shen et al, 2014) and EMF1 in the repression of FLC (Kim et al, 2010). We show here that both EMF1 and AtBMI1 are required for FLC, MAF4, and MAF5 repression, suggesting a PRC1 in which AtRING1, AtBMI1, and EMF1 are required for repression.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…On the other hand, other results suggest that all these components are required for the regulation of a different subset of target genes. For instance, AtRING1A has been shown to participate in the repression of FLC, MAF4, and MAF5 (Shen et al, 2014) and EMF1 in the repression of FLC (Kim et al, 2010). We show here that both EMF1 and AtBMI1 are required for FLC, MAF4, and MAF5 repression, suggesting a PRC1 in which AtRING1, AtBMI1, and EMF1 are required for repression.…”
Section: Discussionmentioning
confidence: 59%
“…As CO transcription is low at ZT1 and its expression is not altered in emf1 and emf2 mutants (Kim et al, 2010), the FT misexpression in these mutants may be CO independent. In support of this, it has been shown that emf1-1/co and emf2/co double mutant phenotypes were indistinguishable from their respective emf1 and emf2 single mutant parents, while emf1-1/ft double mutants usually did not flower and emf2/ft double mutants bolted after producing a higher number of sessile leaves than emf2 single mutants (Haung and Yang, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the function of the LFYasEMF1 misregulated genes restored by ult1-3, we considered the 15 functional categories described previously (Kim et al, 2010), with appropriate modifications of the gene list. These categories include genes involved in flower organ identity, flowering time, seed development, photoreceptor and photosynthesis system, cell expansion, auxin, GA, ethylene, and abscisic acid synthesis and signaling, stress, cold, and heat responses, and histone and transcription factor genes (Supplemental Table S1).…”
Section: Ult1-3 Restored the Misregulated Gene Expression Pattern Ofmentioning
confidence: 99%
“…Mutations in EMF1 and EMF2 cause plants to skip the vegetative phase, transforming the embryonic meristem from an indeterminate to a determinate state and producing a terminal flower (Sung et al, 1992;Yang et al, 1995;Chen et al, 1997;Yoshida et al, 2001). Global gene expression analysis revealed that EMF1 regulates a remarkably high number of genes involved in transcription factor activity, developmental pathways, microRNA gene silencing, and stress responses in Arabidopsis (Kim et al, 2010). Tissue-specific removal of EMF1 activity from leaf primordia in transgenic plants expressing antisenseEMF1 under the control of the LEAFY (LFY) promoter (LFYasEMF1) permits vegetative growth but leads to early flowering plants with upward-curled leaves (Sánchez et al, 2009) similar to those of curly leaf (clf), a PcG mutant (Goodrich et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation